Sewage water and sludge co-implementation effects on soil properties and green chili in Typic Haplustalf of southern India - Sachin, K. S.; Veeranna, H. K.; Dass, Anchal; Harish, M. N.; Bhupenchandra, Ingudam; Rajanna, G. A.; Sannagoudar, Manjanagouda S.; Nithinkumar, Kadagonda; Pratap, Vijay; Niranjan, B. N.; Kumar, G. V. Sumanth; Yogi, Akshay Kumar; et al. (Frontiers in Agronomy, 2026)
Sewage water and sludge provide a viable option to meet crop water and nutrient demands in the face of rising climatic stress. Thus, a 2-year field study (2018 and 2019) was conducted to evaluate the effect of sewage water and sludge on soil properties and the growth response of green chili. The experiment comprised nine treatment combinations involving three types of irrigation water: normal water (I1), treated sewage water (I2), untreated sewage water (I3) along with three soil amendments: farmyard manure (FYM) at 25 t ha−1 (SA1), sewage sludge at 25 t ha−1 (SA2), and a mix of sewage sludge at 12.5 t ha−1 + FYM at 12.5 t ha−1 (SA3). Soil-available nutrient status of N, P, and K increased by ˜10%–15%, ˜14%–20%, and ˜13%–18%, respectively, in I3 and SA2. Sewage water and sludge application further improved soil microbial populations, which included actinomycetes, fungi, and bacteria. Concurrently, multivariate analysis of variance (MANOVA) demonstrated a positive influence of irrigation and soil amendments on soil properties. Across both study years, I3 and SA2 recorded a higher mean green chili yield, with an improvement of approximately 25% over I1 and SA1. Hence, the findings reveal the feasibility of harnessing sewage water resources as sustainable inputs, advancing both resource efficiency and short-term agricultural sustainability in the region.